Перша знахідка Gibellulopsis fusca в Україні - Гавриш, П.В. (Київ : Інститут ботаніки ім. М.Г. Холодного НАН України, 2021)
Gibellulopsis fusca (Thirum. & Sukapure) Giraldo López & Crous, isolated from the rotten hypocotyl of Apium graveolens L., is registered in Ukraine for the first time. Culture identification was made due ITS-region sequence.
Havrysh P.V. First find of Gibellulopsis fusca in Ukraine
Keywords: fungi; biodiversity; Apium graveolens; Ukraine